Maternal Anemia in the Third Trimester and Related Maternal and Fetal Outcomes: Results from a Study in Jember Regency - Devi Arine Kusumawardani; Farhan Dwi Purnama; Andrei Ramani (Window of Health : Jurnal Kesehatan, 2026)
Anemia in pregnant women is at risk of becoming one of the causes of poor maternal and fetal outcomes. Specific interventions to increase hemoglobin levels in anemic pregnant women may significantly influence maternal and fetal outcomes. Jember Regency is one area in East Java Province that is prioritized for reducing cases of poor maternal and fetal outcomes. This quantitative, analytical, and observational study used a cross-sectional design. The study population comprised third-trimester pregnant women from January to December 2022 in the Arjasa Health Center's working area, totaling 550 women. The sample size calculation yielded a sample of 115 third-trimester pregnant women by simple random sampling. The analysis test used in this study was the contingency coefficient test. Data collection used secondary data from the maternal and child health clinic register book, the pregnant women's cohort book, and the Arjasa Health Center laboratory examination book for 2022. The study results showed that the majority of respondents did not have a history of anemia, and those who did mostly had mild anemia (42.6%). The study revealed a correlation between anemia history in third-trimester pregnant women and maternal outcomes (p-value = 0.005, C = 0.291), categorized as a weak correlation, and low birth weight (p-value = 0.015, C = 0.220), also categorized as a weak correlation. The analysis of the history of anemia incidents in third-trimester pregnant women with the age of delivery and infant mortality did not show a significant correlation. Maternal anemia in third-trimester pregnant women is associated with a higher risk of poor maternal outcomes and low birth weight. Strengthening early anemia screening and adherence to iron–folic acid supplementation, integrated into maternal nutrition programs with robust referral systems, is essential to reduce adverse maternal outcomes and low birth weight in Jember Regency.